FENOMENA LINUX, SUATU TEROBOSAN NETWORK ORGANIZATION DALAM ERA PEMASARAN RELASIONAL - Dudi Anandya (Journal of Management and Business, 2003)
Linux is an operating system that it's presence offer many "new concepts" to the market. It’s an open source software developed under GNU project using General Public License (GPL), that gives everyone freedom to run, copy, distribute, study, change, and improve the software. The GNU Project was launched in 1984 to develop a complete Unix-like operating system which is free software: the GNU system. GNU is a recursive acronym for "GNU's Not Unix”; it is pronounced “guh-NEW", In Other way we can say that Linux developed, manufactured, and distributed by it's own costumers. They joined together in the Linux communities and create a network among them. It has a unique lateral pattern of relationship. The Author named all of this as the “Linux Phenomenon". This articles will begin by explaining theories about network, and then discuss the and then discuss the Linux phenomenon. Later, the author will explore the Linux's "breakthrough" in networking, and the implication of "how to do business".